Predictors of cognitive and physical decline: Results from the Health Aging and Body Composition Study - Handing, Elizabeth P.; Hayden, Kathleen M.; Leng, Xiaoyan Iris; Kritchevsky, Stephen B. (Frontiers in Aging Neuroscience, 2023)
Background Risk factors for cognitive decline and physical decline have been studied independently, however older adults might experience decline in both areas i.e., dual decline. Risk factors associated with dual decline are largely unknown and have significant implications on health outcomes. The aim of this study is to explore risk factors associated with dual decline. Methods Using data from the Health, Aging and Body Composition (Health ABC) study, a longitudinal prospective cohort study, we examined trajectories of decline based on repeated measures of the Modified Mini-Mental State Exam (3MSE) and the Short Physical Performance Battery (SPPB) across 6 years (n=1,552). We calculated four mutually exclusive trajectories of decline and explored predictors of decline: cognitive decline (n = 306) = lowest quartile of slope on the 3MSE or 1.5 SD below mean at baseline, physical decline (n = 231) = lowest quartile of slope on the SPPB or 1.5 SD below mean at baseline, dual decline (n = 110) = lowest quartile in both measures or 1.5 SD below mean in both measures at baseline. Individuals who did not meet criteria for one of the decline groups were classified as the reference group. (n= 905). Results Multinomial logistic regression tested the association of 17 baseline risk factors with decline. Odds of dual decline where significantly higher for individuals at baseline with depressive symptoms (CES-D >16) (Odds Ratio (OR)=2.49, 95% Confidence Interval (CI): 1.05-6.29), ApoE-ε4 carrier (OR= 2.09, 95% CI: 1.06-1.95), or if individuals had lost 5+lbs in past year (OR=1.79, 95% CI: 1.13-2.84). Odds were significantly lower for individuals with a higher score on the Digit Symbol Substitution Test per standard deviation (OR per SD: 0.47, 95% CI 0.36-0.62) and faster 400-meter gait (OR per SD= 0.49, 95% CI: 0.37-0.64). Conclusion Among predictors, depressive symptoms at baseline significantly increased the odds of developing dual decline but was not associated with decline in the exclusively cognitive or physical decline groups. APOE-ε4 status increased the odds for cognitive decline and dual decline but not physical decline. More research on dual decline is needed because this group represents a high risk, vulnerable subset of older adults.